2022
DOI: 10.1038/s41598-022-06046-5
|View full text |Cite
|
Sign up to set email alerts
|

The low abundance of CpG in the SARS-CoV-2 genome is not an evolutionarily signature of ZAP

Abstract: The zinc finger antiviral protein (ZAP) is known to restrict viral replication by binding to the CpG rich regions of viral RNA, and subsequently inducing viral RNA degradation. This enzyme has recently been shown to be capable of restricting SARS-CoV-2. These data have led to the hypothesis that the low abundance of CpG in the SARS-CoV-2 genome is due to an evolutionary pressure exerted by the host ZAP. To investigate this hypothesis, we performed a detailed analysis of many coronavirus sequences and ZAP RNA b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The molecular mechanisms underlying the restriction of SARS-CoV-2 by ZAP still need to be elucidated, as well as the different antiviral responses observed between ZAP isoforms and the involvement of ZAP cofactors in viral restriction [51]. Afrasiabi et al (2022) [137] showed that the low frequency of CpG dinucleotides in SARS-CoV-2 is not a result of evolutionary pressure mediated by ZAP activity. This leaves the question unanswered and calls for further investigation into other evolutionary forces that may have led to the decrease in CpG frequency in SARS-CoV-2 [137,138].…”
Section: Coronaviridae Familymentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanisms underlying the restriction of SARS-CoV-2 by ZAP still need to be elucidated, as well as the different antiviral responses observed between ZAP isoforms and the involvement of ZAP cofactors in viral restriction [51]. Afrasiabi et al (2022) [137] showed that the low frequency of CpG dinucleotides in SARS-CoV-2 is not a result of evolutionary pressure mediated by ZAP activity. This leaves the question unanswered and calls for further investigation into other evolutionary forces that may have led to the decrease in CpG frequency in SARS-CoV-2 [137,138].…”
Section: Coronaviridae Familymentioning
confidence: 99%
“…Afrasiabi et al (2022) [137] showed that the low frequency of CpG dinucleotides in SARS-CoV-2 is not a result of evolutionary pressure mediated by ZAP activity. This leaves the question unanswered and calls for further investigation into other evolutionary forces that may have led to the decrease in CpG frequency in SARS-CoV-2 [137,138].…”
Section: Coronaviridae Familymentioning
confidence: 99%